Dietary Behavior and Compliance to Bulgarian National Nutrition Guidelines in Patients With Type 1 Diabetes With Longstanding Disease - Pancheva, Rouzha; Dimitrov, Lyubomir; Gillon-Keren, Michal; Tsochev, Kaloyan; Chalakova, Tatyana; Usheva, Natalya; Nikolova, Silviya; Yotov, Yoto; Iotova, Violeta (Frontiers in Nutrition, 2022)
Introduction: Nutrition education attempts to maintain and enhance good eating habits to achieve optimal metabolic control in people with type 1 diabetes (T1D). Recommendations for patients with T1D are comparable to those of the general population. This study aimed to investigate dietary habits and adherence to nutritional recommendations of patients with T1D as compared with age, gender, and BMI matched people in Bulgaria. Methods: A case-control study included 124 patients with T1D with long disease duration (mean duration 25.3±8.2years) followed up at a diabetes clinic in Varna, Bulgaria for 2 years (2017-2019) and 59 controls matched for gender, age and BMI. A 24-hour dietary recall method was used to assess the nutrition of both groups. A standardized questionnaire was applied to assess the frequency of food consumption (Feel4Diabtes). Height and weight were standardly measured, and BMI was calculated. Findings were compared with Bulgarian recommendations and reference values for energy and nutrient intake for healthy adults. The data were analyzed with the statistical package SPSSv21.0 and Jamovi v.22.5.. Results: The nutritional characteristics of T1D men and women differ. Men with T1D had a higher intake of total carbohydrates (CHO) (U= 734; p= 0.009), a lower intake of total fats (U=728; p= 0.007), and monounsaturated fatty acids (U=795; p= 0.029) as a percentage of total daily energy compared with the controls. Women with T1D had a different distribution of energy intake per meal compared to controls: they consumed more energy (U=378; p= 0.001) and a corresponding share of CHO for lunch, less for dinner (U=493; p=0.015) and had a higher overall healthy diet score when compared to controls (U=440; p=0.02). Adherence to dietary recommendations (e.g. CHO, total fats, saturated fat, ﬁbres) was low in both genders, but lower in the general population compared to people with T1D. Conclusion: Our data demonstrate that people with T1D consume a healthier diet than the general population, which could be attributed to healthier diet awareness, still far from the recommendations. Introduction of annual consultations with a dietitian may improve long-term outcomes.